Tribute : Mamat Khalid - Che Mahadi, Muhammad Hanafi (Universiti Teknologi MARA, Perak, 2022)
Mamat Khalid was a known and beloved director for some of the most well received films in Malaysia. As a tribute, a poster was done in an illustrated style with comedy setting genre in which Mamat Khalid was known for in order to honor him.